Чувствительность личинок настоящих комаров (Diptera, Culicidae) некоторых районов УССР к ядохимикатам - Лоскот, В.М.; Францевич, Л.И. (Вестник зоологии, 1967)
Susceptibility to DDT, BHC, parathion, and dipterex was studied in 14 species of mosquito larvae of more than 60 populations in different areas of the Dnieper basin and the Crimea. The evaluation of the susceptibility levels was made by the dosage-time method in field tests. The effect of the temperature on the toxicity was studied in the laboratory, and the thermal coefficients of toxicity were determined for six preparations. Parathion was the most toxic of all tested insecticides for mosquito larvae. The susceptibility of the larvae varied within broad limits, both interspecifically, and in different populations of the same species. The interspecific variability of the susceptibility to dipterex and parathion exceeded the intraspecific (interpopulational) variability, and the both were nearly equal for DDT and BHC.